Conditions of Aquatic Biodiversity Around the Port of Pototano, District of West Sumbawa - Ahmad Jupri; Hilman Ahyadi; Rachmawati Noviana Rahayu (Jurnal Biologi Tropis, 2023)
Pototano Harbor is one of the locations that crosses a potential marine conservation area, namely the Gili Balu Marine Tourism Park Area.The use of the Pototano port location as a port location has long existed before the formation of the waters area of the Gili Balu water tourism park. This area consists of eight groups of islands which are characterized by beautiful beaches, hills, mangrove forest areas and also the beauty of underwater ecosystems. Natural conditions that support abundant biodiversity make this area have several ecosystems in the aquatic environment, including coral reefs, sea grasses and mangroves. This study aims to determine the condition of the biodiversity of the surrounding watersPototano Port and Core ZoneGili Balu Tourism Park Areanamely Gili Belang, Gili Paserang and Gili Namuby increasing knowledge and human resources regarding water area management. This area has both positive and negative values.The results showed that the highest level of diversity in coral reef ecosystems and seagrass ecosystems was found in the Core Zone of TWP Gili Balu, namely Gili Belang with 86% and 80.8% coverage.The diversity of mangrove species in the four locations is relatively the same, but the abundance or individual density of each species is relatively different.Conditionwaters in the research location classifieddry waters and under normal conditions or not pollutedbecause it has an abundance of plankton communitiesas big 62,33 Eng/L with the most common type is Thalassionema frauenfeldii and Chaetoceros tortissimus.